Inversion Recovery Ultrashort TE MR Imaging of Myelin is Significantly Correlated with Disability in Patients with Multiple Sclerosis - Jang, H.; Ma, Y.-J.; Chang, E.Y.; Fazeli, S.; Lee, R.R.; Lombardi, A.F.; Bydder, G.M.; Corey-Bloom, J.; Du, J. (American Journal of Neuroradiology, 2021)
BACKGROUND AND PURPOSE: MR imaging has been widely used for the noninvasive evaluation of MS. Although clinical MR imaging sequences are highly effective in showing focal macroscopic tissue abnormalities in the brains of patients with MS, they are not specific to myelin and correlate poorly with disability. We investigated direct imaging of myelin using a 2D adiabatic inversion recovery ultrashort TE sequence to determine its value in assessing disability in MS.MATERIALS AND METHODS: The 2D inversion recovery ultrashort TE sequence was evaluated in 14 healthy volunteers and 31 patients with MS. MPRAGE and T2-FLAIR images were acquired for comparison. Advanced Normalization Tools were used to correlate inversion recovery ultrashort TE, MPRAGE, and T2-FLAIR images with disability assessed by the Expanded Disability Status Scale.RESULTS: Weak correlations were observed between normal-appearing white matter volume (R = –0.03, P = .88), lesion load (R = 0.22, P = .24), and age (R = 0.14, P = .44), and disability. The MPRAGE signal in normal-appearing white matter showed a weak correlation with age (R = –0.10, P = .49) and disability (R = –0.19, P = .31). The T2-FLAIR signal in normal-appearing white matter showed a weak correlation with age (R = 0.01, P = .93) and disability (R = 0.13, P = .49). The inversion recovery ultrashort TE signal was significantly negatively correlated with age (R = –0.38, P = .009) and disability (R = –0.44; P = .01).CONCLUSIONS: Direct imaging of myelin correlates with disability in patients with MS better than indirect imaging of long-T2 water in WM using conventional clinical sequences.ANTsAdvanced Normalization ToolsEDSSExpanded Disability Status ScaleGMLlong-T2 GMGMSshort-T2 GMIR-UTEinversion recovery prepared UTENAWMnormal-appearing white matterUTEultrashort TEWMLlong-T2 WMWMSshort-T2 WM